Evaluating the impact of stress reduction interventions as supportive approach in patients with depressive disorder - Sevak, Sanjay; Balalmurugan, G. (International Journal Of Community Medicine And Public Health, 2025)
Depressive disorder is widely recognized as a significant global health challenge, impacting 350 million people worldwide. Stress reduction interventions have emerged as an essential nonpharmacological approach to managing depression, complementing pharmacological treatments. This review examines how stress reduction interventions can reduce stress and depression severity among patients with depressive disorder. A wide-ranging electronic literature search identified studies that satisfied the predefined criteria using PubMed, Medline, Google Scholar and Cochrane Library. Key findings from the majority of the studies indicate relaxation techniques interventions, yoga interventions, cognitive behavioural therapy, complementary therapies, self-awareness interventions and mindfulness as predominant therapeutic strategies in the reduction of stress and depression. These interventions also improved quality of life, social adaptability, resilience and reduced anxiety. Practicing stress reduction interventions might be a useful element of multi-component treatment modalities in a patient with depressive disorder. Further research is needed to expand its application in multimodal stress reduction interventions and incorporate them into clinical practice to enhance outcomes for patients with depression.